2017
DOI: 10.1016/j.clml.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Generic Imatinib Therapy Among Jordanians: An Observational Assessment of Efficacy and Safety in Routine Clinical Practice

Abstract: This study suggests that the efficacy and safety of generic imatinib in this Middle Eastern population in routine clinical practice are comparable to patented imatinib, and to that of the global population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The 12‐month progression‐free and overall survival rates were 92% and 100%, respectively, and most (85%; n = 144) adverse events were mild. The authors concluded that the efficacy and safety of GI was comparable to that of BI in their Middle Eastern population . The largest cohort investigated comes from a study in India, which compared 1067 patients treated with BI with 144 patients treated with GI.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…The 12‐month progression‐free and overall survival rates were 92% and 100%, respectively, and most (85%; n = 144) adverse events were mild. The authors concluded that the efficacy and safety of GI was comparable to that of BI in their Middle Eastern population . The largest cohort investigated comes from a study in India, which compared 1067 patients treated with BI with 144 patients treated with GI.…”
Section: Introductionmentioning
confidence: 83%
“…23 In an observational study from Jordan, the efficacy and safety of GI in 91 adult patients with CML was assessed. 24 Thirty-three patients received GI as first-line therapy, and 58 switched from BI to GI after a median of 4.5 years (range: 0.5-13.6). The 12-month progression-free and overall survival rates were 92% and 100%, respectively, and most (85%; n = 144) adverse events were mild.…”
Section: Size and Characterization Of Cohortsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an indirect suggestion that a well‐regulated and quality‐controlled generic imatinib can maintain the same efficacy of its original form. Many trials evaluated switching from original to generic imatinib and reported no difference in efficacy and safety between the two forms . Kang et al evaluated 30 patients in Canada who switched to generic imatinib (Apotex‐TEVA) and reported loss of MMR in one patient and loss of CHR in one patient with all other patients maintaining their response.…”
Section: Discussionmentioning
confidence: 99%